Analisis Daya Saing Usahatani Jagung pada Lahan Kering di Kabupaten Tanah Laut Kalimantan Selatan - Ahmad Yousuf Kurniawan (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
Corn demand in the world and domestic market inceases with the development of corn-based feed and food industries. During 1990-2007, imported corn inceased 10.46 per cent each year. On the other hand, South Kalimantan has dryland area potency which can be used for corn farming. This research are purposed to analize competitive and comparative advantages of dryland corn farming in Kabupaten Tanah Laut, South Kalimantan. The Policy Analysis Matrix (PAM) was used to determine the competitiveness. Through this matrix, the criterion of private cost ratio (PCR) and domestic resources cost ratio (DRCR) which refer to competitive and comparative advantage, respectedly, could be calculated. The result showed that corn commodity in Kabupaten Tanah Laut was profitable dan it has competitive and comparative advantages. In other words, corn farming in Kabupaten Tanah Laut was able to finance its domestic inputs. However, some policies were needed in order to transform this competitiveness potency to be reality, such as: reduce market distortion, encourage research and development, and provide phisical and economic infrastructures.